Space and Equipment Constraints during Online Practice-Based Learning Faced by Future Physical Education for Elementary School Teachers - Kharisma Akbar Yasri; Trie Maylita Sari; Rifa Hijra Fauziah; Qistina Zulfany; Wulandari Putri (Universitas Pendidikan Indonesia, 2022)
The transition of face-to-face learning to online learning during Covid-19 pandemic brought challenges for Physical Education students, especially in practice-based courses. In online learning, the students were required to provide the space and equipment themselves. Therefore, this study was aimed at determining the constraints related to space and tools faced by Physical Education students in attending online practice-based lectures during the Covid-19 pandemic. This research is qualitative exploratory research using a questionnaire constructed based on Student Survey guidelines of Shape America 2020. The questionnaire was created in Google Form and distributed via WhatsApp. The participants were 93 Physical Education Teacher Education for Elementary School students of a University in Indonesia. The results showed that most students had a limited size of room. The solution taken was mostly looking for other places, usually a field. Most students also had limited tools. For unavailable equipment, the majority of students modified the simple tool available. It indicates that online learning brought challenges for PE students in practice-based courses related to the availability of tools and space. It is recommended that lecturers give directions for creating safe and efficient equipment.